Analisis Efektivitas Pengendalian Internal IT Berdasarkan Metode Cobit 2019 - Dinata, Aria; Majduddin; Sutabri, Tata (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
The implementation of effective information technology (IT) internal control is essential in ensuring optimal IT governance and supporting the achievement of organizational goals. This study aims to analyze the effectiveness of IT internal control based on the COBIT 2019 framework. The research methods used were surveys, in-depth interviews, and document analysis in a company that has implemented COBIT 2019 for three years. The results showed that the effectiveness of IT internal control was measured through the five main domains of COBIT 2019, with an average score above 4, indicating effective implementation. The Monitor, Evaluate, and Assess domain recorded the highest score (4.4), reflecting the company's success in continuous monitoring and evaluation. In addition, the implementation of this framework has succeeded in reducing IT security incidents by 50% in the last three years. However, the Build, Acquire, and Implement domain had the lowest score (4.0), indicating the need for improvement in project management and new technology acquisition. This study confirms that the COBIT 2019 framework is an effective tool for improving IT internal control. Recommendations for strengthening implementation include increased training, periodic evaluations, and adoption of new technologies to support the sustainability of IT governance. Keywords—IT internal control, COBIT 2019, IT governance, effectiveness, risk assessment